2022
DOI: 10.3390/molecules27248679
|View full text |Cite
|
Sign up to set email alerts
|

Blackcurrant (Ribes nigrum L.) Seeds—A Valuable Byproduct for Further Processing

Abstract: The rational exploitation of byproducts is important from the point of view of their potential applicability in various fields. In this study, the possibility of further processing of blackcurrant seeds (BCs), which are a byproduct of fruit processing, was investigated. BCs were used as a material for the extraction of oil on a semi-industrial scale, and the residues were assessed in terms of their potential application in skin care products. Supercritical fluid extraction (SFE) using CO2 at pressures of 230 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…In any case, most compounds found here were previously reported in Ribes species. For instance, Wójciak et al [19], reported the black currant seed glucoside and rutinoside derivatives of quercetin and kaempferol, in addition to the aglycones of most compounds reported here. However, to the best of our knowledge, this paper is the first to report on some compounds occurring in Ribes taxa, such as fisetin, luteolin, eriodictyol, phloretin, galangin, and naringenin, as well as some of their glycosides.…”
Section: Phenolic Compound Profilesmentioning
confidence: 65%
“…In any case, most compounds found here were previously reported in Ribes species. For instance, Wójciak et al [19], reported the black currant seed glucoside and rutinoside derivatives of quercetin and kaempferol, in addition to the aglycones of most compounds reported here. However, to the best of our knowledge, this paper is the first to report on some compounds occurring in Ribes taxa, such as fisetin, luteolin, eriodictyol, phloretin, galangin, and naringenin, as well as some of their glycosides.…”
Section: Phenolic Compound Profilesmentioning
confidence: 65%
“…The research material consisted of seed remains after extraction of oil and it was provided from Łukasiewicz Research Network-New Chemical Syntheses Institute in Puławy (Poland). The extraction of oil was carried out using an in-house-built quartertechnical installation for supercritical CO 2 extraction on scale [18].…”
Section: Plant Materialsmentioning
confidence: 99%
“…Human skin fibroblast cell lines (ATCC ® CRL-2522™, Manassas, VA, USA) were cultured in conditions given in literature [18]. The cells at density of 1 × 10 5 cells/well were treated with varying concentration of the extracts for 24, 48 and 72 h to assess cytotoxicity.…”
Section: Cell Line Assaymentioning
confidence: 99%
“…This aligns with the core tenets of the circular economy, advocating for the efficient utilisation of resources and the adoption of contemporary processing methodologies. Byproducts encompass not only pomace resulting from juice or oil extraction but also various other plant morphological components, such as leaves (e.g., black currant), husks, stems, peels, and seeds, as specified by Staszowska-Karkut et al [ 44 ], Blejan et al [ 39 ], and Wójciak et al [ 45 ], which exhibit substantial polyphenol and fibre content. Leveraging such byproducts represents a reservoir of valuable nutrients, recognised as a cost-effective resource offering manifold health benefits for both consumers and producers, fostering an environmentally sustainable and economically viable food chain [ 46 ].…”
Section: Further Perspective Of Developmentmentioning
confidence: 99%